The California Tobacco Control Program's effect on adult smokers: (3) Similar effects for African Americans across states. Issue 2 (30th March 2007) - Trinidad, Dennis R; Messer, Karen; Gilpin, Elizabeth A; Al-Delaimy, Wael K; White, Martha M; Pierce, John P
Abstract : Objective: To compare trends in African-American (AA) and non-Hispanic white (NHW) smoking between states categorised as having three different levels of tobacco control practice in the 1990s. Setting and participants: Analysis of 1992–3 to 2001–2 Tobacco Use Supplements to the Current Population Survey for differences in adult (20–64 years) daily smoking prevalence for AAs and NHWs across states: California (CA; high cigarette price/comprehensive programme), New York (NY) and New Jersey (NJ; high cigarette price/no comprehensive programme), and tobacco growing states (TGS; low cigarette price/no comprehensive programme). Results: From 1992–3 to 2001–2, there were large declines in AA smoking across states (2.7–3.8% decrease/year, adjusted for age, income, education, gender; p<0.05). Adjusted NHW smoking prevalence declined significantly only in CA. AA prevalence declined significantly and did not differ across state groups. In all years, in all state groups, adjusted prevalence was either not significantly different or was lower for AAs than for NHWs. More recent cohorts of AAs appeared to have taken up smoking at lower rates than older cohorts. Conclusion: There were uniformly large declines in AA smoking from 1992–3 to 2001–2 across states, independent of type of tobacco control strategy. Further research is needed into factors associated with smoking declines among AAs.